2003
DOI: 10.1093/hmg/ddg142
|View full text |Cite
|
Sign up to set email alerts
|

Association of Eotaxin gene family with asthma and serum total IgE

Abstract: The Eotaxin gene family (Eotaxin1, Eotaxin2 and Eotaxin3) recruits and activates CCR3-bearing cells such as eosinophils, mast cells and Th2 lymphocytes that play a major role in allergic disorders. To date, the effect of polymorphisms of Eotaxin genes on asthma phenotypes has not been thoroughly examined. In our research, we sequenced whole regions of the Eotaxin gene family to identify polymorphisms, which may be involved in the development of asthma and total serum IgE. We have identified 37 SNPs in the Exot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 40 publications
(11 reference statements)
4
27
0
Order By: Relevance
“…Association of SNPs and haplotypes of eotaxin-2 gene with the plasma eotaxin-2 level Of the 16 SNPs identified in our previous study (Shin et al 2003), five SNPs were selected for larger-scale genotyping based on linkage disequilibriums (LDs) among SNPs and frequencies. Four polymorphisms (+734G fi A, +824C fi A, +1102T fi G, and +1193 fi A) showing low frequencies (<0.10) were excluded for further analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Association of SNPs and haplotypes of eotaxin-2 gene with the plasma eotaxin-2 level Of the 16 SNPs identified in our previous study (Shin et al 2003), five SNPs were selected for larger-scale genotyping based on linkage disequilibriums (LDs) among SNPs and frequencies. Four polymorphisms (+734G fi A, +824C fi A, +1102T fi G, and +1193 fi A) showing low frequencies (<0.10) were excluded for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Genotyping by single-base extension (SBE) and electrophoresis Primer extension reactions were performed with a SNaPshot ddNTP Primer Extension Kit (Applied Biosystems, Foster City, CA, USA), as described (Shin et al 2003). The DNA samples containing extension products and GeneScan 120-Liz-size standard solutions were added to Hi-Di formamide (Applied Biosystems).…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the single nucleotide polymorphisms (SNPs) in the eotaxin gene family were identified (Shin et al, 2003;. We previously reported that the Eo2 +179T C, Eo2 +275C T of eotaxin-2 and the Eo3 +2497T G of eotaxin-3 are significantly associated with susceptibility to asthma, and also demonstrated that the Eo3 +2497T G is related to serum total IgE level, and to the peripheral blood eosinophil counts in asthma patients .…”
Section: Introductionmentioning
confidence: 99%